"Life Death" in Plato and Derrida: A Review of Michael Naas's Plato and the Invention of Life: Plato and the invention of life, by Michael Naas, New York, Fordham University Press, 2018, 288 pp., $32.00 (pbk), ISBN: 978-0823279685. Issue 1 (2nd January 2020) - Marren, Marina
ABSTRACT: Michael Naas's Plato and the Invention of Life, which I review in this essay, formulates the question that is at the core of Plato's thought. This question is: What is life? Naas's inquiry into life indicates a field for prolific research in ancient and continental philosophy, as it calls on us to rethink the difference, the priority, and the relationship between beings and Being. Our understanding of this coupling, which first set into motion the "gigantomachia" of Western philosophy, depends on retracing Plato's view of life which, as Naas brilliantly shows through recourse to Derrida, is invested with death through and through.